-2-5x=-2(1+4x)

Simple and best practice solution for -2-5x=-2(1+4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2-5x=-2(1+4x) equation:


Simplifying
-2 + -5x = -2(1 + 4x)
-2 + -5x = (1 * -2 + 4x * -2)
-2 + -5x = (-2 + -8x)

Add '2' to each side of the equation.
-2 + 2 + -5x = -2 + 2 + -8x

Combine like terms: -2 + 2 = 0
0 + -5x = -2 + 2 + -8x
-5x = -2 + 2 + -8x

Combine like terms: -2 + 2 = 0
-5x = 0 + -8x
-5x = -8x

Solving
-5x = -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-5x + 8x = -8x + 8x

Combine like terms: -5x + 8x = 3x
3x = -8x + 8x

Combine like terms: -8x + 8x = 0
3x = 0

Divide each side by '3'.
x = 0

Simplifying
x = 0

See similar equations:

| 1/2*b*19.8 | | 7g+8=22 | | 0.2x=-0.7 | | R=1-2n+5 | | 4x+4x+3=0 | | 14-12=x/-4 | | 5x/4-3=7x/6 | | 17-3(4-3x)=6x-1 | | (-2z/y^3)^2 | | 1/3(m-3n)=2 | | 3x(-5)/2x | | 0.55=logx | | -4-p=8p-5(6+7p) | | (3xy^2-2y)=0 | | f(2e^4)=lnx | | 2=4-2f | | 81/54 | | 10x-20=-5x+10 | | -15=-k-4k | | x-.15x=7849.08 | | 4a^2-6a^6/8a^-3 | | x+6+3x=-18 | | 6-14=z/-4 | | 30+.5x=1.25x | | x+(-7)=-77 | | x-.15x=4812.96 | | 4.25z=4.5z-6.25+6.25 | | x^2+4x+8y+1=0 | | x^2+10x+y+20=0 | | -3b+9=15 | | -3k-4-1=7 | | -3b+9= |

Equations solver categories